The origins of the idea of personal rights and freedoms in international agreements of the Modern Era (XV – beginning of the XX century) - Fomina, L. O.; Syroid, T. L. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
Introduction. The issue of the origins of the idea of human rights and freedoms is one of the fundamental questions in the history of law, philosophy and international relations. Its significance is increasing in the context of modern globalisation processes, as human rights are viewed not only as an internal matter for a particular state, but also as a universal value recognised by the international community. Recognising that the concept of human rights has a long historical background enables us to gain a deeper understanding of the nature of contemporary international legal norms and principles that regulate the protection of human dignity, freedom and equality. Particular attention should be paid to the Early Modern period (15th–early 20th centuries), when the modern system of international relations took shape, state sovereignty principles were consolidated, and treaties began to reflect humanitarian ideas more explicitly. Summary of the main research results. The article explores the origins of the idea of human rights and freedoms in Early Modern international treaties (15(th) – early 20(th) centuries) and traces the evolution of humanitarian principles in state treaty practices. It demonstrates that the development of the concept of human rights has deep historical and philosophical roots linked to humanism, the Reformation, natural law and the Enlightenment. The study reveals how international treaties, under the influence of these ideas, gradually began to include provisions aimed at limiting the cruelty of war, protecting religious and national minorities, combatting slavery, and affirming the principles of tolerance and humanity. Particular attention is given to analysing the Peace of Westphalia (1648), the Acts of the Congress of Vienna (1815), the Congress of Berlin (1878), the Geneva Convention (1864) and the Hague Peace Conferences (1899 and 1907). It is substantiated that during this period, the conceptual and normative prerequisites for the modern system of international human rights protection were formed. Conclusions. The authors conclude that the international treaties of the Early Modern period laid the foundation for the transition from fragmented humanitarian norms to the universal recognition of the intrinsic value of human beings, as well as for the formation of modern international humanitarian and human rights law.